2015
DOI: 10.1152/ajpheart.00564.2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hypoxia increases calcium affinity of BK channels in ovine fetal and adult cerebral artery smooth muscle

Abstract: Tao X, Lin MT, Thorington GU, Wilson SM, Longo LD, Hessinger DA. Long-term hypoxia increases calcium affinity of BK channels in ovine fetal and adult cerebral artery smooth muscle. Am J Physiol Heart Circ Physiol 308: H707-H722, 2015. First published January 16, 2015; doi:10.1152/ajpheart.00564.2014.-Acclimatization to high-altitude, long-term hypoxia (LTH) reportedly alters cerebral artery contraction-relaxation responses associated with changes in K ϩ channel activity. We hypothesized that to maintain oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…However, studies on smooth muscle cells isolated from cerebral arteries demonstrated a decline of BK Ca channels activity during ontogenesis. The BK Ca ‐current in ovine basilar artery myocytes of fetuses was shown to be enlarged in comparison to adult animals because of a higher calcium sensitivity of BK Ca channels, their augmented phosphorylation by protein kinase G and increased clustering in the plasma membrane . Presumably, the high activity of BK Ca channels observed in patch‐clamped fetal cerebrovascular myocytes is not seen at the functional level because of a dramatically decreased frequency of calcium sparks, necessary for the activation of BK Ca channels in cerebral arteries…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on smooth muscle cells isolated from cerebral arteries demonstrated a decline of BK Ca channels activity during ontogenesis. The BK Ca ‐current in ovine basilar artery myocytes of fetuses was shown to be enlarged in comparison to adult animals because of a higher calcium sensitivity of BK Ca channels, their augmented phosphorylation by protein kinase G and increased clustering in the plasma membrane . Presumably, the high activity of BK Ca channels observed in patch‐clamped fetal cerebrovascular myocytes is not seen at the functional level because of a dramatically decreased frequency of calcium sparks, necessary for the activation of BK Ca channels in cerebral arteries…”
Section: Discussionmentioning
confidence: 99%
“…A high activity of these types of potassium channels in the circulatory system of 10‐ to 15‐day‐old animals can serve as a mechanism keeping peripheral resistance and blood pressure low in the immature cardiovascular system thereby reducing the risk of vessel injury/remodelling. Of note, the functional role of vascular potassium channels can be altered in early ontogenesis by intrauterine stress and fetal hypoxia . Such developmental abnormalities can have detrimental cardiovascular consequences later in adulthood .…”
Section: Discussionmentioning
confidence: 99%
“…74 After the same period of exposure to H-ALT, increased activity (more sensitive to activation and higher affinity for Ca 2+ ) of large-conductance Ca 2+ -activated K + channels (BK) was found in basilar arteries of ovine adults. 75 This behavior of cerebral arteries could favor an increased CBF during H-ALT exposure, 75 since in vascular smooth muscle cells, BK channel opening favors K + efflux and hyperpolarization, with subsequent closure of voltage-dependent Ca 2+ channels, decreased intracellular Ca 2+ , and vasodilation. 76…”
Section: Pathways Of Bp Regulation At H-altmentioning
confidence: 99%
“…Native BK channels exhibit a wide range of biophysical, pharmacological, and functional properties that differ among various cell types (Ding, Li, & Lingle, 1998; Gessner et al, 2005; Jones, Gray-Keller, Art, & Fettiplace, 1999; Xia, Ding, & Lingle, 1999), at different stages of development (Carvalho-de-Souza, Varanda, Tostes, & Chignalia, 2013), and in different physiological or pathological conditions (Hu et al, 2011; Manzanares et al, 2015; Tao et al, 2015). BK channels with slightly different biophysical properties can be produced by alternative splicing of KCNMA1 precursor mRNA at several different sites (Glauser, Johnson, Aldrich, & Goodman, 2011; Ramanathan, Michael, Jiang, Hiel, & Fuchs, 1999; Saito, Nelson, Salkoff, & Lingle, 1997; Schreiber, Yuan, & Salkoff, 1999; Yu, Upadhyaya, & Atkinson, 2006).…”
Section: Introductionmentioning
confidence: 99%